Comparison of Hemodynamic Changes After the Insertion of Laryngeal Mask Airway Versus Endotracheal Intubation - A. Pushparani; G. Mirunalini; Getsyal (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
Background and Aims: Serious hemodynamic deviations can arise with endotracheal intubation, which leads to a short but evident Cardiovascular response. The aim of this study is to observe the hemodynamic responses after the insertion of laryngeal mask airway and endotracheal intubation. Study Design: This is a randomised controlled study. Place and Duration of Study: The study was organized at SRM Medical College and Research Center, Kattangulathur, 603203, India over the course of one year. Methodology: Sixty patients, varying in age between eighteen to sixty, were divided into two comparable groups at random: 30 belonged to Group 1 (LMA) and 30 to Group 2 (ETT). Heart rate (HR), blood pressure (SBP & DBP), and oxygen saturation were measured at baseline, during induction, and at the 0th, 3rd, and 5th min following successful intubation in each group in order to evaluate the hemodynamic response. Results: Patients in both groups had stable vitals. The mean HR, DBP, SBP and oxygen saturation between the Group LMA and Group ETT were analyzed. After statistical analysis with an independent student t-test was found to be statistically significant (p < 0.05) for mean HR, SBP and DBP whereas mean oxygen saturation was found to be statistically insignificant (p >0.05). Conclusion: The study concludes that the laryngeal mask airway for short (<60 mins) surgical procedures causes less hemodynamic changes when compared with endotracheal intubation.